ANTI BULLYING PROJECT “STOP BULLYING EVERYWHERE, EVERY TIME, AND FOR EVERYONE ” TO STRENGTHEN THE PANCASILA STUDENT PROFILE - Yulianti Yulianti; Maulana Fajar Wandhiro; Endang Setyaningsih (Magister Scientiae, 2023)
The limited understanding of teachers in implementing the project method in strengthening the profile of Pancasila students has an impact on the implementation of learning in class. The impact that occurs in the classroom is the lack of formation of the character profile of Pancasila students such as mutual cooperation and global diversity. This study aims to describe the project " No Bullying happens everywhere, everytime, and to anyone" as a strengthening of the profile of Pancasila students. This research uses a type of qualitative research with a descriptive approach. The research subjects were teachers, parents and children of class VI. Two teachers became participants who were selected through a purposive sampling technique. Data collection techniques used are interviews, observation, and documentation. Data analysis techniques use the Miles and Huberman models. The results of the study show that the project " no bullying happens everywhere, everytime, and to anyone" arises when children experience bullying trauma which often happens to them and their classmates, they feel uncomfortable at school so they want to find solutions to problems by discussing and identifying bullies . The mutual cooperation character is stimulated when children can work together to identify, discuss activities and students are able to show concern for fellow friends and are willing to share experiences in dealing with bullying. Meanwhile, the attitude of global diversity can be seen in the attitude of understanding each other's language, the cultural accent of each friend, being able to collaborate with anyone and being friends with everyone.